2013
DOI: 10.1071/wf12140
|View full text |Cite
|
Sign up to set email alerts
|

Short-term physiological effects of smoke on grapevine leaves

Abstract: In recent years, bushfires and prescribed burns have caused substantial economic loss to the wine industry due to smoke taint, which makes wine unpalatable. Considerable research is being done to ameliorate smoke taint but the information available about the effect of smoke on grapevines is limited. We examined the physiological effects of short-term exposure to smoke on leaves of several varieties of grapevines. Gas exchange was measured before and after short-term exposure of leaves to smoke that was produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 73 publications
0
27
0
Order By: Relevance
“…The impact of desiccation on g s and K leaf varies considerably between species (Brodribb & Holbrook, 2006;Sack & Holbrook, 2006;Brodribb et al, 2009), and is caused in part by the cavitation of leaf veins (Kikuta et al, 1997;Salleo et al, 2000;Nardini et al, 2001Nardini et al, , 2003Cochard et al, 2002;Brodribb & Holbrook, 2003;Johnson et al, 2011), as well as differences in vein architecture (Scoffoni et al, 2011). There is also the intriguing possibility that smoke may provide a cue for stomatal closure that might mitigate the impact of a fire plume (Gilbert & Ripley, 2003;Calder et al, 2010;Bell et al, 2013;Aerts, 2015). However, our simulations were based on an assumption of a constant cuticular conductance that was unaffected by the heating of the leaf.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of desiccation on g s and K leaf varies considerably between species (Brodribb & Holbrook, 2006;Sack & Holbrook, 2006;Brodribb et al, 2009), and is caused in part by the cavitation of leaf veins (Kikuta et al, 1997;Salleo et al, 2000;Nardini et al, 2001Nardini et al, , 2003Cochard et al, 2002;Brodribb & Holbrook, 2003;Johnson et al, 2011), as well as differences in vein architecture (Scoffoni et al, 2011). There is also the intriguing possibility that smoke may provide a cue for stomatal closure that might mitigate the impact of a fire plume (Gilbert & Ripley, 2003;Calder et al, 2010;Bell et al, 2013;Aerts, 2015). However, our simulations were based on an assumption of a constant cuticular conductance that was unaffected by the heating of the leaf.…”
Section: Discussionmentioning
confidence: 99%
“…Smoke alters UV profiles, obscures sunlight, provides substrates for water and ice condensation, and deposits particulates on plants and the environment. These processes occur both within burn perimeters (Bell, Stephens, & Moritz, 2013) and beyond via atmospheric transport. Aerosol radiative forcing is also a major uncertainty in our understanding of the net effects of fire on Earth's climate (Landry, Matthews, & Ramankutty, 2015).…”
Section: Fire Behaviour Directs Ecological Outcomesmentioning
confidence: 99%
“…Other research, however, has shown little effect on the physiology of grapevines from short‐term exposure of leaves to smoke for the grapevine cultivars Cabernet Franc, Cabernet Sauvignon, Chardonnay, Durif, Pinot Noir and Syrah, irrespective of fuel type (Bell et al. ). Assimilation, stomatal conductance and transpirational levels in most cultivars had recovered to pre‐smoke levels within 48 h of initial smoke application (Bell et al.…”
Section: Uptake Translocation Carry‐over Between Growing Seasons Pmentioning
confidence: 99%
“…Assimilation, stomatal conductance and transpirational levels in most cultivars had recovered to pre‐smoke levels within 48 h of initial smoke application (Bell et al. ). It was also noted that the length of exposure time, concentration of smoke components, vine phenology and the interplay of other plant stresses, such as drought, nutrient limitation, competition for water with other plants and high temperature, may also play an important role in plant recovery after exposure to smoke (Bell et al.…”
Section: Uptake Translocation Carry‐over Between Growing Seasons Pmentioning
confidence: 99%
See 1 more Smart Citation